PENGARUH PENGGUNAAN MEDIA SOSIAL FACEBOOK TERHADAP PERILAKU CYBERBULLYING PADA SISWA SMAN 12 PEKANBARU - Nurjanah, Siti; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Social media evoles with the delopment of technology. The number of social media user have increased every years. As a result, the user got negative and positif impacts from the social media One of the effects of the use of social media is the emergence of cyberbullying behavior. Cyberbullying is behavior intended to humiliate, frighten, injure or cause harm to the weaker party by using the means of information technology, especially social media facebook. The purpose of this study was to determine whether there is any influence using of social media facebook to cyberbullying behavior of the students in SMAN 12 Pekanbaru.The method used in this study is a quantitative method with explanatory survey, researchers collected data using questionnaires. The location of this research is in SMAN 12 Pekanbaru. The number of samples for this study as many 195 respondents, using techniques random sampling. To determine how much influence these two variables, researchers used a simple linear regression analysis. Processing test data questionnaire using Statistic Program Product Of Service Solution (SPSS) windows version 17.The results of this study indicate that the imfluence using of social media facebook to cyberbullying behavior of students in SMAN 12 Pekanbaru, the regression coefficient values obtained in this study is Y = 2.954 +0.267 X with a significance level of 0.035 is less than α = 0.05. This means that there were had influence of social media using facebook to cyberbullying behavior in 2.3% with a very weak category, this means that negative behaviors teens using social media facebook is a bit, because teenagers have entered at a good level and wise in choosing and using social media facebook, the balance o 97.7% influenced by other variables outside in this study.Keywords: social media, facebook, cyberbullying behavior